Teachers’ perception and experience on outcomes-based education implementation in Isabela State University - Krichelle A. Tungpalan; Mila F. Antalan (International Journal of Evaluation and Research in Education (IJERE), 2021)
The existing typology established by the Commission on Higher Education (CHED) and the introduction of outcomes-based education (OBE) has created numerous demands and challenges for higher education in the Philippines. Hence, this study analyzed the scope of expertise and experience of Isabela State University-College of Computing Studies, Information and Communication Technology faculty members in the 2nd semester of study year 2018-2019 to identify OBE implementation. In this study, a mixed-method approach was used for data and information collection. Weighted mean was used to interpret the extent of knowledge and actual practice of the faculty members and on the qualitative part, data were analyzed using thematic analysis. The results of this study indicate a great deal of expertise and experience on the implementation of OBE among the faculty members of the College of Computing and Information Communication Technology at Isabela State University Cauayan Campus. The faculty members are well versed in the application and practice of OBE and will continue to contribute to the realization of the goals of OBE by practice.